Profile of neonates born with congenital birth defects in a tertiary care hospital of North India: An observational study - Abhilasha Sinha; Shalini Tripathi; Nitu Nigam; Mala Kumar; S.N. Singh (Elsevier, 2022)
Objectives: India shares largest burden of congenital birth defects (CBDs) in the world. There is paucity of data on the CBDs in our region of the country. Methods: This was a hospital based observational study to find incidence, risk factors and outcome of CBDs among live neonates. Results: Of 7,075 babies, 92 had 124 CBDs, making the incidence 1.3%. The system predominantly involved was musculoskeletal system (52.2%) followed by central nervous system (28.3%), genitourinary system (26.1%). Among the single CBDs, congenital talipes equino varus (27.4%) was the commonest followed by spina bifida (11.2%) and cleft palate (6.4%). The significant factors associated with CBD were no antenatal visits (p = 0.041), TORCH and/or VDRL positivity (p = 0.023), gestational diabetes mellitus (GDM) (p = 0.007), hypertension (p = 0.090), consanguinity (p = 0.03), no intake of folic acid (p = 0.015). Of these, factors found significant on logistic regression were GDM (OR 3.44; p = 0.018), maternal hypertension (OR 4.88; p = 0.011), consanguinity (OR 13.55; p = 0.028) and no intake of iron/folic acid (OR 5.53; p = 0.001). Of the 92 neonates with CBD, 44 (47.8%) were discharged, 28 (30.5%) expired, 20 (21.7%) left against medical advice. Conclusion: Incidence of CBD was comparable to previous Indian studies. Consanguinity, no intake of folic acid, maternal hypertension and GDM were associated risk factors. About half neonates with CBD expired or left against medical advice. This shows dismal outcome of neonates with CBD in this region.